-1 = 4a - 2b +c .......................(1)

2= a + b + c ....................................(2)

-16= 9a + 3b + c .............................(3)

subtract eqn (2) from (1) that means, (1) - (2) ; and also subtract eqn (2) from (3) that means, (3) - (2) ; we got,

-3 = 3a -3b .....................(4)

-18 = 8a + 2b ..................(5)

divide eqn (4) by 3 ; and eqn (5) by 2, we got,

-1 = a - b ...............................(6)

-9 = 4a + b .............................(7)

add these eqns (6) and (7)

- 10 = 5a

a = -2

put this value of "a" in eqn (6)

we got, b = -1

now, put these values of "a" and "b" in eqn (2) and find out "c". Finish it.